'Project Piedemonte': between the Maloti-Drakensberg and the Great Escarpment in the Eastern Cape Province, South Africa. (August 2020) - de la Peña, Paloma; Witelson, David M.
Abstract: Abstract : A new project maps mobility patterns and social networks from prehistory to historical times in the western piedmont of the Maloti-Drakensberg, South Africa, and considers how rock art sites relate to seasonal or transhumance patterns in the region.